Quantitative vulnerability assessment of Corda river water basin: impacts of seasonality on water quality in the State of Maranhao - Cavalcanti, Késia Gomes da SIlva; da Silva, Darlan Ferreira; Lima, Neuriane SIlva; Mendonça, Rita de Cássia; Nunes Neto, Wallace Ribeiro; Chagas Silva, Maria Raimunda (Ciência e Natura, 2020)
The Corda river is the main source of fresh water for recreation, leisure, supply and irrigation to the municipality of Barra do Corda - MA. The objective of the present study was to evaluate the physicochemical parameters of Corda river’s water using the methodology described by the American Public Health Association. The water samples were collected in the seasonal period spanning between February and September of the year of 2018. The parameters which were analyzed during the study were pH, conductivity, turbidity, total dissolved solids and salinity, besides concentrations of nitrite, nitrate, and total phosphorus. Three principal components were identified during the PC Analysis. Those components explain more than 74% of the total variance observed during the rainy and dry season. Axis 1and 2 included variables which were related to quality of water and could be affected by the change in seasons. The results indicated that pH (7.11), P (2,82 mg L-1), NO3- (3,23 mg L-1), turbidity (35.82 NTU) and conductivity (35.83 µS/cm) parameters were most affected by changing from rainy to dry season.